ASSESS THE LEVEL OF ANXIETY AMONG RELATIVES OF THE PATIENT ADMITTED IN INTENSIVE CARE UNIT IN SELECTED HOSPITAL - MS. D. ARUL ANNUNCIA; MRS. S. SUJITHRA (International Journal of Pharma and Bio Sciences, 2016)
Introduction: Human mind can be addressed as the most complicated system in this world. It is very difficult to own the machine in a normal quality. Anxiety is not same for all people it has been observed that these are individual difference in taking a stressful situation. Hence the anxiety management has become are essential life style present day. Objectives: To assess the level of anxiety among the relatives of the patient waiting outside the intensive care units. To associate the level of anxiety with selected demographic variables. Methodology: Exploratory and descriptive design was adopted. Total 50 patient relatives were selected by simple randomized method from intensive care unit at Saveetha medical College and hospital, thandalam. The data was collected, organized and analyzed in terms of both descriptive and inferential statistics. The study result showed that 16%of the samples had showed mild level of anxiety, but majority of samples 40% ranged under moderate level of anxiety and 28% of the samples were enclosed under moderate to severe level of anxiety, it also depicts that only 16% of the sample sector comes under severe level of anxiety. This study implies that relatives of the patients who are waiting outside the intensive care units will have mild to severe level of anxiety.